Evaluasi faktor-faktor penentu profitabilitas bank umum syariah di indonesia dengan net operating margin sebagai variabel moderating - Novitasari, Aditya Ayuk; Annisa, Arna Asna (Journal of Accounting and Digital Finance, 2023)
This research analyzes the effect of capital adequacy ratio, operational costs on operational income, and financing-to-deposit ratio on profitability (ROA) with net operating margin as a moderating variable. This type of research is quantitative research with secondary data in panel form. The population in this research is 14 Sharia Commercial Banks in Indonesia for the 2016-2020 period. Sample selection used the purposive sampling method. The analysis technique used is moderated regression analysis. This study found that the capital adequacy and financing-to-deposit ratios did not affect the return on assets. Meanwhile, operational costs on operating income (BOPO) hurt asset return. Net Operating Margin can moderate the variables Capital Adequacy Ratio, Operational Costs to Operating Income (BOPO), and financing to deposit ratio to return on assets of Sharia commercial banks